Histological variation of early stage atherosclerotic lesions in baboons after prolonged challenge with high-cholesterol, high-fat diet - Karere, Genesio M. (J Med Primatol, 2019)
INTRODUCTION: The baboon is a well-characterized model of human early stage atherosclerosis. However, histological and morphological changes involved in atherogenesis in baboons are not known. Previously we challenged baboons with a high-cholesterol, high-fat diet for two years and observed fatty streak and plaque lesions in iliac arteries (RCIA). METHODS: We evaluated histological and morphological changes of baboon arterial lesions and control arteries. In addition, we evaluated the vascular expression of CD68 and SMαA markers with progression of atherosclerosis. RESULTS: We observed changes that correlated with extent of atherosclerosis, including increased maximum intimal thickness. We demonstrated at molecular level the infiltration of smooth muscle cells and macrophages into the intimal layer. Further, we observed histological and morphological discordancy between the affected and adjacent areas of the same RCIA. CONCLUSION: Atherogenesis in baboons is accompanied by histological, morphological and molecular changes, as in humans, providing insights to evaluate the mechanisms underlying early stage atherosclerosis in target tissues.